2010
DOI: 10.1017/s109285290002736x
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate Effect in Children With ADHD Can Be Measured by an Ecologically Valid Continuous Performance Test Embedded in Virtual Reality

Abstract: Background: Continuous performance tasks (CPTs) embedded in a virtual reality (VR) classroom environment have been shown to be a sensitive and user-friendly assessment tool to detect cognitive deficits related to attention-deficit/hyperactivity disorder (ADHD). The aim of the current study was to compare the performance of children with ADHD on a VR-CPT while on and off treatment with methylphenidate (MPH) and to compare the VR-CPT to a cgrrently used CPT, Test of Variables of Attention (TOVA).Methods:Twenty-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 22 publications
3
34
0
1
Order By: Relevance
“…The virtual environment CPT yielded similar case-control effect sizes as the classical CPT from the Test of Variables of Attention (T.O.V.A.) [47], and was also sensitive to MPH treatment effects [48]. This approach may afford the opportunity to conduct assessments with higher ecological validity without losing experimental rigor.…”
Section: Neuropsychological Characteristicsmentioning
confidence: 79%
“…The virtual environment CPT yielded similar case-control effect sizes as the classical CPT from the Test of Variables of Attention (T.O.V.A.) [47], and was also sensitive to MPH treatment effects [48]. This approach may afford the opportunity to conduct assessments with higher ecological validity without losing experimental rigor.…”
Section: Neuropsychological Characteristicsmentioning
confidence: 79%
“…There is also a need to utilize other clinical tools for assessing ADHD symptoms. Recently, CPT embedded in a virtual reality has emerged as a user‐friendly assessment tool . CPT is widely used in the assessment and study of patients with ADHD .…”
Section: Discussionmentioning
confidence: 99%
“…In a number of studies, methylphenidate is shown to improve symptoms measured on CPT to the extent that children with ADHD treated with methylphenidate can perform nearly as well as a control group [9,12,[14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Others have investigated the use of CPT in a virtual setting or as an online test that can be made in the child's home or at school, to create a naturalistic setting [11,17].…”
Section: Introductionmentioning
confidence: 99%